Factors associated with medication errors in the psychiatric ward of Razi Hospital in Tabriz: Perspectives of nurses - Abdi M; Piri Sh; Mohammadian R; Asadi Aghajeri M; khademi E (Zanjan University of Medical Sciences and Health Services, 2018)
Background: Medication errors are considered to be the most significant safety threatening factors for the patients in hospital, to which many factors contribute. Objectives: This study was conducted to determine the role of associated factors in the incidence of medication errors in the psychiatric ward of Razi Hospital in Tabriz from the perspectives of nurses in 2017. Methods: In this descriptive cross-sectional study, we selected 150 nurses working in the psychiatric ward of Razi Hospital in Tabriz through random sampling method. The data collection instrument included a demographic and researcher-made questionnaire to assess the effective factors in the incidence of medication errors according to the perspectives of nurses. The data were imported into SPSS version 20 and analyzed via ANOVA and Chi-square tests. Results: In this study, 95(63.3%) women and 55(36.7%) men with the mean age of 34.4±0.66 participated. The highest mean score for the causes of medication errors was related to the professional errors made by nurses (33.93±2.61) and the structure of the psychiatric ward (27.96±5.8). The change in Kardex during the transfer of the patient to other wards was the most significant cause of errors with a mean of 4.35±5.53. The mean score of medication errors was significantly different with that of the level of education, age, work experience, and employment types. However, it was not significantly different with that of gender, marital status, nurse job position, and shift work rotation. Conclusion: Considering the incidence of the most common medication errors in the field of nursing careers and structure of psychiatric ward, we recommend that nurse managers increase the skills of medication administration through holding training courses and improve the physical conditions of the ward